2012
DOI: 10.3233/wor-2012-0903-5639
|View full text |Cite
|
Sign up to set email alerts
|

An international validation study of the care thermometer: a tool supporting the quality of ergonomic policies in health care

Abstract: Occupational back pain among nurses leads to high costs and personal suffering for nurses. It is difficult to assess the success of such initiatives and to monitor results in a practical way. Such a practical monitoring and web-based instrument was developed. This Care Thermometer (CT) allows the users to assess the current situation in their facility today, and, with regular use, it can help to track progress over time. The Care Thermometer is a further step in the development of the TilThermometer, a validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Second, selection might have occurred since participation of nursing homes and hospitals was on a voluntary basis and targeted those that employed ergocoaches on wards. 24 These organisations may have been more focussed on preventing high physical load. 25 The actual use of ergonomic devices in this study may, therefore, be higher than in a random sample of nursing homes and hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Second, selection might have occurred since participation of nursing homes and hospitals was on a voluntary basis and targeted those that employed ergocoaches on wards. 24 These organisations may have been more focussed on preventing high physical load. 25 The actual use of ergonomic devices in this study may, therefore, be higher than in a random sample of nursing homes and hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, no simple, feasible and validated scale exists for determining the individual residents’ need for physical assistance. Existing systems, such as the Care Thermometer, RAI or MAPO Method, provides risk assessment in the manual handling of residents, primarily aiming to estimate the physical function of the resident or pinpoint which ergonomic equipment and/or preventive measures are needed in caring for the residents [ 8 , 9 , 10 , 11 , 12 ]. While this is also useful, these systems are quite extensive and burdensome for regular use.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they do not give the information needed for daily distribution of residents, with different physical assistance needs, between workers within teams in eldercare. Nonetheless, these existing systems have not been validated against observations of the residents’ physical assistance needs, but against self-registration or other assessment tools [ 10 ]. Thus, we need a simple, feasible and validated tool to assess the resident’s need for physical assistance in eldercare.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it gives a clear indication of the risk involved in PH (low, moderate, high) [ 17 ]. A previous study has shown the TilThermometer to be valid for use in international care facilities for risk assessment of PH [ 21 ]. The study was performed in the UK, USA, Germany and the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…The TilThermometer covering five mobility groups has already been translated from Dutch into English [ 21 ]. However, it has not yet been translated into Swedish and so far there have been no research studies using this risk assessment instrument in a Swedish context.…”
Section: Introductionmentioning
confidence: 99%